PENGEMBANGAN MODEL ANALISIS RELASI BAHASA DAN INTERNET BERBASIS PARADIGMA CMDA (COMPUTER MEDIATED DISCOURSE ANALYSIS) - Saifullah, Aceng Ruhendi (Jurnal Pendidikan Bahasa dan Sastra, 2017)
Dalam dekade terakhir, kajian tentangÂ  relasi bahasa, media, dan teknologi komunikasi telah menjadi kajian lintas disiplin yang menarikÂ  perhatian para ahli dari berbagai disiplin ilmu. Lebih khusus, dalam kaitannya dengan kajian wacanaÂ  di Internet, penggunaan bahasa di InternetÂ  dipandang sebagai pertanda lahirnya â€œnew genreâ€ sekaligus sebagai the state of the art dalam kajian wacana, yang dikenal sebagai kajian computer mediated discourse analysis (CMDA). Â Dalam konteks perkembangan itu, kajian ini dimaksudkan untuk merumuskan modelÂ  analisis relasi bahasa dan Internet berbasis CMDA. Pertanyaannya, â€œsejauh mana paradigma CMDAÂ  dapat dirumuskan sebagai model pengembangan analisis relasi bahasa dan Internet. Kajian ini menemukan, bahwa ragam bahasa di Internet tidak sepenuhnya menunjukkan ciri-ciri ragam tulis, akan tetapi cenderung menunjukkan ciri-ciri â€œragam lisan yang dituliskanâ€. Di samping itu, ditemukan pula, bahwa konteks media dan konteks situasi komunikasi tampak berpengaruh secara signifikan dalam menentukan makna suatu tuturan di Internet.Â  Dengan demikian, paradigma CMDA dalam kajian wacana di Internet tampak relevan digunakan, terutama untuk mengindentifikasi ragam bahasa dan makna tuturan di Internet.Kata kunci: konteks media; konteks situasi komunikasi; Internet; computer mediated discourse analysis (CMDA)In the last decade, the study of language relations, media, and communications technology has become an interdisciplinary study that attracts the attention of experts from various disciplines. More specifically, in relation to the study of discourse on the Internet, the use of language on the Internet is seen as a sign of the birth of "new genre" as well as the state of the art in discourse studies, known as computer mediated discourse analysis (CMDA). In the context of this development, this study is intended to formulate models of analysis of language and Internet relationships based on CMDA. The question centers on the extent to which the CMDA paradigm can be formulated as a model for the development of language and Internet relation analysis. This study reveals that the variety of languages on the Internet does not fully show the characteristics of writing, but tends to show the characteristics of "written verbal". In addition, the analysis showed that the context of the media and the context of the communication situation seemed to have a significant effect on determining the meaning of a speech on the Internet. Thus, the CMDA paradigm in the study of discourse on the Internet seems relevant to use, especially to identify the variety of languages and meanings of speech on the Internet.Keywords: media context; context of communication situation; Internet; computer mediated discourse analysis (CMDA)